STRUKTUR KEUANGAN : STUDI PERBANDINGAN ANTARA PERUSAHAAN DI SURABAYA DAN PERUSAHAAN TIDAK TERDAFTAR - Fajar Purwanto (STIE Mahardhika, 2019)
In detail, we conducted a differential analysis of the financial structure, as measured as a debt-to-equity ratio (D/E), comparing European-listed companies with similar unregistered companies. The analysis covers the period 2015-2017. The main samples of listed and unregistered companies are grouped into nine sub samples representing many sectors of the economy: Health, Consumer Cycle, Non-cyclical Consumers, Energy, Industry, Basic Materials, Technology, Telecommunications and Utilities. We compare the average debt-to-equity ratio for listed and unregistered companies, to different sectors to verify whether in listed companies the incidence of debt is lower than for unregistered companies as stated from the majority literature. Then, we calculate the difference between mean as